Gaps in patient-centered follow-up cancer care: a cross sectional study. Issue 2 (4th March 2021) - Hobden, Breanne; Turon, Heidi; Waller, Amy; Carey, Mariko; Proietto, Anthony; Sanson-Fisher, Rob
Abstract: Objective There are published guidelines on the care that should be provided to cancer patients upon finishing treatment (i.e. follow-up care). Gaps in care may arise where patients' reported experiences of care do not align with guideline recommendations. The aim of this study was to explore whether oncology patients report gaps in patient-centered follow-up care. Methods This study was a cross-sectional survey of adult cancer patients receiving follow-up care within four outpatient oncology clinics. Patients were approached in clinic waiting rooms and asked to complete an electronic survey. The survey examined patients' self-report of receiving six aspects of follow-up care. Results A total of 239 participants completed the survey (study consent rate = 83%). Only 49% of participants received all six items of care. Patients reported high rates of being told who to contact if they have any questions or concerns (95%); who to contact if signs or symptoms occur (91%); and what to expect in their follow-up care (90%). A lower proportion of patients indicated they were informed about the role of their GP after treatment has finished (79%); what symptoms or signs might suggest the cancer had returned (74%); or were given a written care plan (71%). Conclusions : The study highlights that there is a gap between some aspects of optimal patient-centered care, and the actual care received by patients. Health care providers and researchers should consider how to improve follow-up care experiences to ensure best practice cancer care delivery during this important stage in cancer survivorship.